DEVELOPMENT OF PROJECT BASED OUTDOOR LEARNING TOOLS IN GEOMETRY TO IMPROVE STUDENTS' PROBLEM SOLVING ABILITY - Masrukan Masrukan; Ernita Ernita (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The teaching tools are crucial for teachers in delivering instructional material. However, the development of learning tools that meet content standards and are of high quality is still quite rare. This research aims to develop and evaluate the quality of Project-Based Outdoor Learning (PjBOL) tools for geometry to enhance problem-solving skills. The research sample consists of students from classes VII D and VII E at SMP Negeri 2 Ungaran. The research method used is Research and Development with the Four-D model: Define, Design, Develop, Disseminate. The research instruments include expert assessment sheets, student response sheets, and problem-solving ability tests. Data analysis focuses on validity, practicality, and effectiveness. The results indicate that: (1) the developed PjBOL tools include Learning Objectives Flow, Teaching Modules, and Learning Materials for geometry to enhance problem-solving skills; and (2) the PjBOL tools are of high quality as they meet the criteria of validity, practicality, and effectiveness. The test results show that the problem-solving abilities of students using PjBOL are higher in average and proportion compared to those using Discovery Learning, and there is an improvement in students' problem-solving abilities. Based on these findings, PjBOL tools effectively enhance problem-solving skills. Perangkat pembelajaran merupakan alat yang sangat penting untuk guru dalam menyampaikan materi ajar. Namun pengembangan perangkat pembelajaran yang sesuai dengan standar isi dan berkualitas masih sangat jarang dilakukan. Penelitian ini bertujuan untuk mengembangkan dan menguji kualitas perangkat Project Based Outdoor Learning (PjBOL) materi Geometri untuk meningkatkan kemampuan pemecahan masalah. Sampel penelitian yaitu peserta didik kelas VII D dan VII E SMP Negeri 2 Ungaran. Metode penelitian adalah Research and Development dengan model Four-D yakni Define, Design, Develop, Disseminate. Instrumen penelitian yang digunakan yaitu lembar penilaian ahli, lembar respon peserta didik, dan tes kemampuan pemecahan masalah. Analisis data yang dilakukan adalah kevalidan, kepraktisan, dan keefektifan. Hasil penelitian menunjukkan bahwa; (1) perangkat PjBOL yang dikembangkan meliputi Alur Tujuan Pembelajaran, Modul Ajar, dan Bahan Ajar materi Geometri untuk meningkatkan kemampuan pemecahan masalah, dan (2) perangkat PjBOL berkualitas karena memenuhi kriteria valid, praktis, dan efektif dengan hasil tes tuntas secara klasikal, rata-rata dan proporsi kemampuan pemecahan masalah peserta didik dengan PjBOL lebih dari rata-rata dan proporsi kemampuan pemecahan masalah peserta didik dengan Discovery Learning, serta terdapat peningkatan pada kemampuan pemecahan masalah peserta didik. Berdasarkan hasil penelitian, perangkat PjBOL mampu meningkatkan kemampuan pemecahan masalah.